2009
DOI: 10.1002/mawe.200900505
|View full text |Cite
|
Sign up to set email alerts
|

Human dental follicle precursor cells of wisdom teeth: isolation and differentiation towards osteoblasts for implants with and without scaffolds

Abstract: The human dental follicle is a developmental precursor for essential periodontal tissues such as periodontal ligament and root development. These cells can be expected to differentiate into several lineages, since they are derived from mesoderm. Especially the differentiation towards the osteogenic lineage could be interesting for tissue regeneration with or without growing on scaffold biomaterials in autologous transplantation for reconstruction of large bone defects and incorporation of teeth implants.Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Isolation of human stem cells from the dental follicle (hDFSCs) was performed as described by Haddouti et al 56. from three young donors with healthy periodontal status.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of human stem cells from the dental follicle (hDFSCs) was performed as described by Haddouti et al 56. from three young donors with healthy periodontal status.…”
Section: Methodsmentioning
confidence: 99%
“…Haddouti and colleagues showed that DFCs have a strong commitment towards the osteogenic lineage and show a more quantitative osteogenic differentiation (Haddouti et al, 2009). Thus, DFCs and BCDCs seem to be more committed towards osteogenic lineage.…”
Section: The Characterization Of Atscs Dfcs and Bcdcs For Bone Regenmentioning
confidence: 99%
“…Interestingly, preliminary results obtained with dental follicle MSC of wisdom teeth, isolated during routine dental surgery [41], show that these cells use solely the P3 promoter for the expression of splicing variants (Longo, Tobiasch and Luparello, unpubl. data), thereby suggesting that MSC from different tissue sources may be endowed with differing transcriptional programmings.…”
Section: Discussionmentioning
confidence: 99%